Inhibiting the IRE1α Axis of the Unfolded Protein Response Enhances the Antitumor Effect of AZD1775 in TP53 Mutant Ovarian Cancer. Issue 21 (26th May 2022) - Xiao, Rourou; You, Lixin; Zhang, Li; Guo, Xichen; Guo, Ensong; Zhao, Faming; Yang, Bin; Li, Xi; Fu, Yu; Lu, Funian; Wang, Zizhuo; Liu, Chen; et al.
Abstract: Targeting the G2/M checkpoint mediator WEE1 has been explored as a novel treatment strategy in ovarian cancer, but mechanisms underlying its efficacy and resistance remains to be understood. Here, it is demonstrated that the WEE1 inhibitor AZD1775 induces endoplasmic reticulum stress and activates the protein kinase RNA‐like ER kinase (PERK) and inositol‐required enzyme 1 α (IRE1 α ) branches of the unfolded protein response (UPR) in TP53 mutant (mt TP53 ) ovarian cancer models. This is facilitated through NF‐ κ B mediated senescence‐associated secretory phenotype. Upon AZD1775 treatment, activated PERK promotes apoptotic signaling via C/EBP‐homologous protein (CHOP), while IRE1 α ‐induced splicing of XBP1 (XBP1s) maintains cell survival by repressing apoptosis. This leads to an encouraging synergistic antitumor effect of combining AZD1775 and an IRE1 α inhibitor MKC8866 in multiple cell lines and preclinical models of ovarian cancers. Taken together, the data reveal an important dual role of the UPR signaling network in mt TP53 ovarian cancer models in response to AZD1775 and suggest that inhibition of the IRE1 α ‐XBP1s pathway may enhance the efficacy of AZD1775 in the clinics. Abstract : WEE1 inhibitor AZD1775 disrupts endoplasmic reticulum proteostasis and activates the protein kinase RNA‐like ER kinase and inositol‐required enzyme 1 α (IRE1 α ) arms of the unfolded protein response in ovarian cancer cells with mutant p53, which is mediated by NF‐ κ B‐induced senescence‐associated secretory phenotype. Cotargeting of WEE1 and IRE1 α ‐XBP1s pathway may be synergistic in advanced ovarian cancer with mutant p53.